Event-triggered observer design for output-sampled systems. (December 2021) - Song, Chengcheng; Wang, Haoping; Tian, Yang; Zheng, Gang
Abstract: This paper investigates event-triggered (ET) observers for output-sampled nonlinear state affine systems ( x ̇ = A ( u ) x + b ( u ) ). In particular, the sampling of the system's output is aperiodic and decided by a designed system performance based event-triggered mechanism (ETM). Under this novel ETM, the global exponential stability of the observer system is guaranteed. The continuous state estimation is derived by using aperiodic sampled system output. The effectiveness of the proposed observer has been illustrated on a numerical example. For the special constant case of the considered system ( A ( u ) = A ), an LMI based ET observer is also proposed, and finally compared to the system performance based ET observer in a mobile cart system example.